To Inculcate the Meaning and Importance of Teaching Singing in the Minds of Students in Higher Education - Tursunova Dilorom Djaxonovna (Research Parks Publishing LLC, 2021)
Singing, which is one of the types of musical activity, is also one of the most effective means of educating children in the aesthetic spirit. In fact, the song increases the emotional sensitivity of the child, arouses love for the beauty of nature, life and human relationships, cultivates children's artistic and aesthetic taste.